Performance of chicken broilers fed with diets substituted with mulberry leaf powder - Carlina Freddie, Simol; Andrew Alek, Tuen; Humrawali Hazid, Ahmad Khan; John Keen, Chubo; Patricia Jie Hung, King; Kian Huat, Ong (Academic Journals, 2012)
The effect of substituting commercial broiler diet with mulberry leaf powder on feed intake, growth rate and feed conversion efficiency was studied. Treatment diets were prepared by substituting 20, 30, 40 and 50% with mulberry leaf powder to commercial broiler feed. The crude fibre and crude protein contents of the treatment diets were higher than those of the control (100% commercial feed) but the crude fat content was lower. No significant difference (p> 0.05) in feed intake was observed for broilers fed with diet containing up to ...